2011
DOI: 10.1016/j.neuropharm.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A population of immature cerebellar parallel fibre synapses are insensitive to adenosine but are inhibited by hypoxia

Abstract: Publisher statement: "NOTICE: this is the author's version of a work that was accepted for publication in Neuropharmacology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Neuropharmacology, VOL 61, ISSUE 4, 2011, DOI: 10.1016/j.neuropharm.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…In many of the whole-cell patch-clamp experiments, recordings were made with Cs+ in the pipette, which will block postsynaptic GIRK channels (e.g., see Courjaret et al 2009). In our hands, we found that adenosine had no effect on the firing rate of Purkinje cells (recorded with an extracellular electrode), although activation of GABA B receptors markedly reduced the firing rate (Atterbury and Wall 2011). This contrasts with the findings of Kessler et al (2008) who found in organotypic cerebellar slices that A 1 receptor agonists reduce the firing rate of Purkinje cells and the original findings of Dunwiddie et al (1984) in acute slices and in vivo.…”
Section: Does Adenosine Acting Via Postsynaptic a 1 Receptors Hyperpolarize Cerebellar Neurons?contrasting
confidence: 99%
“…In many of the whole-cell patch-clamp experiments, recordings were made with Cs+ in the pipette, which will block postsynaptic GIRK channels (e.g., see Courjaret et al 2009). In our hands, we found that adenosine had no effect on the firing rate of Purkinje cells (recorded with an extracellular electrode), although activation of GABA B receptors markedly reduced the firing rate (Atterbury and Wall 2011). This contrasts with the findings of Kessler et al (2008) who found in organotypic cerebellar slices that A 1 receptor agonists reduce the firing rate of Purkinje cells and the original findings of Dunwiddie et al (1984) in acute slices and in vivo.…”
Section: Does Adenosine Acting Via Postsynaptic a 1 Receptors Hyperpolarize Cerebellar Neurons?contrasting
confidence: 99%
“…Accordingly, studies have shown that the cerebellum plays an important role in gaze holding (Leigh & Zee, ; Bertolini et al ., ). Because hypoxia induces alterations in the metabolic system of the cerebellum (Serrano et al ., ; Atterbury & Wall, ), it may increase eye instability by disrupting the cerebellar inputs to the neural integrator (Zee et al ., ; Eizenman et al ., ; Aksay et al ., ).…”
Section: Discussionmentioning
confidence: 99%